Prevalence and clinical significance of antikeratin antibodies and other serological markers in Lithuanian patients with rheumatoid arthritis. Issue 5 (1st May 2001) - Vasiliauskiene, L; Wiik, A; Høier-Madsen, M
Abstract : OBJECTIVES: To assess the clinical value of several serological markers in Lithuanian patients with rheumatoid arthritis (RA) compared with control patients with rheumatic disease and age matched healthy controls. METHODS: Serum samples from 96 patients with RA of approximately 8 years' duration, 90 rheumatic disease controls, and 37 healthy subjects were tested. Antikeratin antibody (AKA), antineutrophil cytoplasmic antibody (ANCA), and antinuclear antibody (ANA) titres were estimated by indirect immunofluorescence (IIF) and serum samples positive for ANA and ANCA were further studied by enzyme linked immunosorbent assay (ELISA). IgA and IgM rheumatoid factors (RF) were measured by ELISA. RESULTS: A positive AKA test was highly specific for RA (diagnostic specificity 97%), being found in 44% of the patients. Although both RF tests had a higher sensitivity, they were less specific for RA. ANCA was detected in 33% of patients with RA but lacked diagnostic specificity. AKA and ANCA were associated with more erosive disease and the presence of extra-articular manifestations. Positivity for AKA, IgA RF, and ANCA was significantly associated with disease activity and worse functional capacity. However, in multiple regression analysis only positivity for AKA was significantly correlated with functional disability (p=0.0001), evaluated by the Steinbrocker functional classification, and no single marker had any relation with radiological damage. CONCLUSION: Although AKA showed the highest disease specificity, all serological markers studied except ANA exhibited interesting associations with important clinical and paraclinical parameters of RA.